Local politicians 1979-80 - Local government councillors - Wallin, Gunnar (Stockholm University, 1983)
The survey forms part of the project ´Local government - an evaluation of the reform of amalgamation of municipalities´. The main issues dealt with how the organisation of political representatives looks like, its size, who becomes a local politician, and the working conditions for local politicians. It also deals with the part the political parties play in the parliamentary arena in the municipalities. Another topic is the reasons for people to leave their municipal positions of trust. The study is partly a replication of Local representatives 1968 (SSD 0110).

Studien är en del av projektet för att utvärdera kommunsammanslagningsreformen. De viktigaste frågorna i undersökningen handlar om hur organisationen av de politiska företrädarna ser ut, dess storlek och arbetsvillkoren för lokala politiker. Studien diskuterar även de politiska partiernas roll i den parlamentariska arenan i kommunerna och vilka skäl som kan ligga till grund för politiskt förtroendevalda att lämna sina uppdrag.
Studien är delvis en uppföljning av Kommunala förtroendemän 1968 (SND 0110).
Kommunalpolitikerundersökningen 1979-80 - Kommunfullmäktiges ledamöter
Keywords: local government policy; kommunalpolitik; child care; barnomsorg; local government services; kommunal service; membership; medlemskap; political parties; politiska partier; councillors; fullmäktigeledamöter; Political behaviour and attitudes; Politiska beteenden och attityder; Government, political systems and organisations; Regering, politiska system och organisationer; Political Science; Statsvetenskap